La LÓGICA MATEMÁTICA DESDE LAS DISCIPLINAS CIENTÍFICAS DE INFORMÁTICA - YUDELKIS VALDERRAMA GARRIDO; WALFREDO GONZÁLEZ HERNÁNDEZ (Revista Ingeniería, Matemáticas y Ciencias de la Información)
In this era where social evolution has led humanity to the Information and Knowledge Society, the job of computerengineers is mainly to detect, recognize and solve problems by finding more and more effective computer solutions. Thetraining of engineers in this regard has a basic characteristic: the need to create a very solid logical-mathematical base,so that their performance will be largely governed by an adequate interpretation of the problem and the next search forthe solution. For this reason, the importance of Mathematical Logic and its deep relationship with Computer Science isaddressed, specifying its link with the main disciplines: Database, Programming, Software Engineering, ComputerArchitecture and Artificial Intelligence. It is analyzed, from the point of view of the sciences involved in the formation ofthe computer engineer, how in each of them the impact of Mathematical Logic is evidenced.